GERMINATION AND EPIPHITIC MYCOFLORA OF SWEET MAIZE SEEDS BY THE ACTION OF BIOLOGICAL AND CHEMICAL PROTECTION PRODUCTS - Telichko, L. P. (Scientific Progress & Innovations, 2020)
The influence of biological and chemical preparations on sowing qualities of sweet maize seeds is shown. The importance and role of using biological preparations as one of the main components of modern technol-ogies of environmentally safe sweet maize cultivation have been shown. Conducting the research provides additional knowledge about the effects of factors on field germination capacity, the results of which are aimed at increasing sweet maize yield. The paper presents the results of “Bionorma Pseudomonas” and “Ahriinsecta Triomaks” biological preparations’ effect. “Bionorma Pseudomonas” is a preparation of pro-tective and stimulating action with increased antibacterial and antifungal activity to protect against phyto-pathogenic microorganisms, the causative agents of cultivated plants’ diseases. “Ahriinsecta Triomaks” is a biological insecticide of entomo-pathogenic bacteria and fungi of contact and gastric action. It protects against a wide range of pests. It is a complex biological preparation of entomo-pathogenic bacteria and mi-cromycetes. The varieties of sweet maize, used in the experiment, had different groups of ripeness and were characterized by increased resistance to diseases: that was why they were chosen for the studies. The deter-mination of laboratory germination capacity and the study of seed infection were carried out by germination method in Petri dishes on filter paper and nutrient medium; the influence of the pretreatment on mycobiote was defined by decomposition on nutrient solid medium, and the degree of infection was studied in each var-iant of the experiment. Seeds studied in laboratory experiments were sown on the plots where field germina-tion capacity of sweet maize plants was determined. Field experiments were performed according to the method of starting and conducting experiments with maize. The results of the conducted research testify that in the technology of sweet maize cultivation it is quite possible to replace the application of chemical prepa-rations for pre–sowing seed treatment by biological preparations. The using of biological preparations is a promising direction: due to applying natural mechanisms it is possible to obtain leveled, good plants without causing directed selection and the risk of appearing resistant mycomycetes in agrophytocenosis.